Factors Affecting Persistent Postoperative Pain in Patients with Hip Fractures - Kyo Goto; Hideki Kataoka; Ayana Honda; Junichiro Yamashita; Kaoru Morita; Tatsuya Hirase; Junya Sakamoto; Minoru Okita (Pain Research and Management)
Osteoporotic fractures are common among older people, and hip fractures (HF) can be devastating. Surgery is indicated for most cases of HF, and chronic persistent postoperative pain is likely to occur. This study investigated the multifaceted factors related to persistent pain occurring during the acute phase and subacute phase of recovery after HF surgery. We conducted a prospective 8-week study of older HF patients after surgery. We evaluated pain intensity, depression symptoms, the fear of falling, pain catastrophizing, cognition and attention, the ability to perform activities of daily living, and the physical performance at 2 weeks (acute phase) and at 4 weeks (subacute phase) after surgery. Patients were divided into the light group (Verbal Rating Scale (VRS) score ≤1) and severe group (VRS score ≥2) according to pain intensity at 8 weeks (recovery phase) after surgery. Factors affecting persistent postoperative pain during recovery were examined using logistic regression analysis. Seventy-two patients were analyzed: 50 in the light group and 22 in the severe group. In the severe group, pain with movement and Pain Catastrophizing Scale scores were higher than those of the light group at 2 weeks and at 4 weeks after surgery. The regression analysis showed that pain with movement at 2 weeks and at 4 weeks after surgery and pain catastrophizing at 4 weeks after surgery were related to persistent postoperative pain. HF patients may have persistent pain if they continue to experience pain and catastrophize their pain during the acute phase and subacute phase after surgery.